Neuroscience Integrated PBL (Out of Print) - Edward Klatt; Andrew Payer (Association of American Medical Colleges, 2009)
Abstract This web-based, problem-based learning (PBL) exercise includes a series of 25 pages with progressive unfolding of information regarding a series of clinical cases. The exercise requires the students in each group to keep track of an entire family. Family members may have more than one illness, and those illnesses may impact other family members. The cases are integrated across basic science and clinical science disciplines, with pathology, pharmacology, physiology, behavioral science, and clinical skills subject matter. Students apply their knowledge in previously learned subject matter to the clinical problems. The students also have to learn to identify knowledge gaps and acquire the necessary information to fill these gaps in a timely manner. The students use clinical reasoning and work through differential diagnoses, then explain the pathophysiology of the diseases encountered. Visual materials in the form of gross and microscopic pathologic images and radiologic imaging are built into the cases. Students and faculty who participated in the initial implementation of this work showed enthusiasm, even at the end of the year two curriculum when students were focused on the USMLE Step 1 exam. Student and faculty evaluations (using a scale of 1 = worst to 5 = best) were in the range of 4 to 5. Faculty development time was considerably reduced from that required for the same number of hours applied to case-based small groups, requiring only a single 1 hour session. However, 2 hours of faculty development time devoted to learning about the PBL process were needed, but this was a one-time requirement that could be applied to additional PBL exercises.